Analysis of the Influence of Investment and Human Development on Indonesia’s Economic Growth - Tianamel, Sinta; Badriyah, Nurul (Journal of Development Economic and Social Studies, 2026)
The volatile nature of Indonesia's economic trajectory and the stark regional imbalances observed between 2015 and 2024 necessitate a rigorous re-examination of developmental catalysts, specifically investment and human capital. This research employs a quantitative methodology utilizing panel data across 34 provinces, processed via multiple linear regression with the Fixed Effect Model (FEM) as the primary analytical tool. Empirical findings demonstrate that Domestic Investment (PMDN) fails to exert a significant impact on growth, pointing toward structural inefficiencies in domestic capital allocation and its disproportionate concentration in specific sectors and geographic hubs. Conversely, Foreign Direct Investment (PMA) and the Human Development Index (HDI) both manifest a positive and statistically significant influence, highlighting the critical roles of technological spillover and workforce quality in driving national productivity. Ultimately, these results imply that achieving a resilient and inclusive economic future for Indonesia depends on a strategic shift toward optimizing investment quality and prioritizing holistic human development.